(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Colorectal cancer, a leading global malignancy, often involves dysregulation of apoptosis. Bcl-2, an anti-apoptotic protein inhibiting programmed cell death, is overexpressed in early colorectal carcinogenesis, suggesting a key role in tumor initiation. This study aimed to assess Bcl-2 expression in histologically diagnosed colorectal adenocarcinoma and its association with histopathological grade, stage, and other parameters. Materials and methods: A cross-sectional study of 49 surgically resected colorectal adenocarcinoma specimens was conducted from March 2021 to December 2022 at the Department of Pathology, Chittagong Medical College. Tissue sections underwent Hematoxylin and Eosin (H&E) staining and Bcl-2 immunostaining. Clinical and pathological data were recorded and statistically analyzed. Results: Overall, 85.7% (42/49) of colorectal adenocarcinoma patients showed positive Bcl-2 expression, predominantly moderate (38.8%) and strong (30.6%) staining, while only 14.3% were negative.Bcl-2 positivity was associated with female sex (p=0.029) conventional histopathological type (p=0.001) tumor grade (93.0% and 33.3% in low-grade and high-grade tumors, respectively, p=0.001) and nodal status (p=0.004). Low-grade carcinomas predominantly exhibited moderateto-strong Bcl-2 positivity, while high-grade carcinomas were mostly negative, showing a significant inverse correlation between Bcl-2 expression intensity and tumor grade (p=0.001). No significant associations were found with age, tumor location or depth of invasion. Conclusion: This study demonstrates that reduced or absent Bcl-2 expression in colorectal adenocarcinoma is significantly associated with higher tumor grade and aggressive behavior. These findings suggest Bcl-2 expression profiling holds promise as a prognostic marker and could represent a therapeutic target to promote apoptosis and inhibit early neoplastic growth in colorectal adenocarcinoma. JCMCTA 2025 ; 36 (2): 53-58